Enhanced Integration of Health, Climate, and Air Quality Management Planning at the Urban Scale - Kleiman, Gary; Anenberg, Susan C.; Chafe, Zoe A.; Appiah, Desmond C.; Assefa, Tibebu; Bizberg, Andrea; Coombes, Toby; Cuestas, Doroti; Henze, Daven K.; Kessler, Alexander; Kheirbek, Iyad; Kinney, Patrick; et al. (Frontiers in Sustainable Cities, 2022)
Cities emit the majority of greenhouse gas emissions globally and are increasingly committing to aggressive mitigation actions. Cities are also experiencing poor—and in some cases worsening—air quality, contributing to large disease burdens for adults and children. Integrated planning frameworks can help cities leverage and prioritize measures that achieve climate, air quality, and health benefits simultaneously. We developed and applied an integrated climate action planning process that includes air quality, utilizing Pathways-AQ, a new assessment tool, in six pilot cities: Accra, Ghana; Addis Ababa, Ethiopia; Buenos Aires, Argentina; the metropolitan area of Guadalajara, Mexico; Johannesburg, South Africa; and Lima, Peru. Implementing the “ambitious” greenhouse gas reduction scenarios in these cities' climate action plans would reduce in-city contributions to fine particulate matter (PM2.5) concentrations and would avoid 230–1,040 annual premature deaths per city, by 2050. This new integrated climate action planning process revealed the importance of (i) geographic scales of analysis, (ii) data integration across climate and air quality, (iii) local civic engagement, and (iv) nuanced health messaging. Rapidly scaling up and applying this integrated approach can broaden the group of municipal stakeholders involved in climate-related planning goals, potentially leading to greater ambition by integrating climate, air pollution, and health objectives.